The particularities of acute kidney injury in critically ill patients with COVID-19 - BULAI, Felicia; BANOV, Pavel; CEBAN, Emil (One Health & Risk Management, 2025)
Introduction. Acute kidney injury (AKI) is a common complication in critically ill patients with COVID-19, associated with increased mortality. This study aimed to evaluate the incidence of acute kidney injury in COVID-19 patients hospitalized in intensive care units, identify risk factors for its development, and determine the impact of AKI on mortality and clinical outcomes. Material and Methods. A retrospective cohort study was conducted and included patients with confirmed COVID-19 infection, admitted to the Republican Clinical Hospital “Timofei Moșneaga” between June 01, 2020, and August 31, 2020. The association between potential risk factors and AKI was assessed using relative risk (RR) with 95% confidence intervals (CI). Results. Of the 81 patients included, 20 (24.69%) developed AKI. Significant risk factors associated with AKI included mechanical ventilation (RR = 7.96; 95% CI: 2.86–22.15, p < 0.001) and vasopressor therapy (RR = 4.12; 95% CI: 1.43–11.86, p = 0.009). The mortality rate was significantly higher in patients with AKI compared to those without AKI (90% vs. 36.06%, RR = 2.49; 95% CI: 1.85–3.36, p < 0.001). Conclusions. Acute kidney injury is a severe complication in critically ill COVID-19 patients and significantly increases mortality among patients hospitalized in intensive care units. Identifying modifiable risk factors could help optimize management strategies and improve survival rates.